2021
DOI: 10.3390/nu13051417
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tart Cherry (Prunus cerasus, cv Montmorency) Concentrate Supplementation for 3 Months on Cardiometabolic Risk Factors in Middle-Aged Adults: A Randomised, Placebo-Controlled Trial

Abstract: Background: Tart Montmorency cherries (MC) have been shown to be rich in anthocyanins and other phytochemicals known to have anti-inflammatory properties and influence pathways that might improve cardiometabolic health. However, there is limited evidence for the longer-term use of tart cherries on these indices. The aim of the current study was to investigate the influence of MC concentrate on cardiometabolic health indices following a 3-month supplementation period. Methods: Fifty middle-aged adults (34 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 69 publications
(111 reference statements)
2
33
0
Order By: Relevance
“…This data is in line with the work by Lear ( 25 ) who found a decrease in insulin sensitivity (decreased Matsuda index), with an increase in insulin and no decrease in blood glucose in those supplementing with MTC juice. Additionally, Chai et al ( 28 ) found an increase in blood glucose following 12 weeks of MTC concentrate ingestion, while Kimble et al ( 52 ) found no impact of 12 weeks MTC concentrate ingestion on blood glucose levels. Interestingly, a seven day intervention in patients with metabolic syndrome found a significant decline in blood glucose and an increase in insulin ( 53 ), which suggests in the short-term, supplementation may improve insulin sensitivity, but this does not appear to translate to long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This data is in line with the work by Lear ( 25 ) who found a decrease in insulin sensitivity (decreased Matsuda index), with an increase in insulin and no decrease in blood glucose in those supplementing with MTC juice. Additionally, Chai et al ( 28 ) found an increase in blood glucose following 12 weeks of MTC concentrate ingestion, while Kimble et al ( 52 ) found no impact of 12 weeks MTC concentrate ingestion on blood glucose levels. Interestingly, a seven day intervention in patients with metabolic syndrome found a significant decline in blood glucose and an increase in insulin ( 53 ), which suggests in the short-term, supplementation may improve insulin sensitivity, but this does not appear to translate to long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiometabolic health and other variables, as described in detail below, will be assessed at baseline and after 20 days (post-intervention). In agreement with previous trials of cardiometabolic health, the primary outcome measure will be the between-group difference in systolic blood pressure from baseline to post-intervention [ 27 ]. Secondary outcome measures will be between-group differences in anthropometric, energy expenditure and substrate oxidation (during rest and physical activity), haematological, blood pressure/resting heart rate, psychological wellbeing and sleep efficacy indices.…”
Section: Methodsmentioning
confidence: 99%
“…After the conclusion of their baseline data collection session, participants will be provided with either Montmorency tart cherry, blueberry or placebo concentrate. Participants will be required to consume 30 mL of supplement diluted in 100 mL of water twice daily: once in the morning and again in the evening [ 27 ]. All supplementations will be kept refrigerated throughout.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with anthocyanin intake with implications for athletes have not had the intake duration as is common for clinical studies [e.g., 3 months tart cherry: ( 44 ); 6 months blueberry: ( 45 )]. For normobaric hypoxia and fed state conditions ( 28 , 29 ), future studies are needed to examine the effects of intake duration and higher doses of anthocyanins on exercise performance.…”
Section: Future Directions For Sport and Exercise Nutrition Research ...mentioning
confidence: 99%